Plan exportador de cacao procedente de Coper, Boyacá (2020)
Colombia has climatic and land conditions, ideal fields for the production of fine-grain, soft cocoa and an excellent aroma. Therefore, in the world and within international trade; This product, especially Colombian, is recognized for being of high quality, as is Colombian Coffee, except that cocoa has not had great support from the government; encouraging production and processing. According to Procolombia, fine and aromatic cocoa is a category that groups only 5% of the world-wide commercialized bean (International Cocoa Organization, ICCO). And in the case of Colombia, this bean is select and exclusively for the production of fine chocolates due to its acidity and balance. Due to its characteristics, cocoa is a product in constant growth that offers specific and preferential prices in the international market. By 2015 Colombia had exported US $ 74 million to 33 countries, including: Mexico, Spain and the United States. The purpose From this export plan is to analyze the current market, its development, its potential, the importance and possibilities of export to the final target market, Today Colombia has great opportunities in the international market, and this representation is one of them, and the progress that has been carried out to carry out the surfaces of international stature, it has been a path that is opened for this association of products, but it is important to clarify that it is not only to encourage commercial relations with other countries, but also research, innovation that will lead us to a development of quality products which represents greater advantages with international competition.